The Impact of Adverse Employment and Working Conditions on the Risk of Workplace Injury in Canada - Victoria Nadalin (Elsevier, 2021)
Background: Employment standards (ES) include having a regular payday, regular breaks, the right to paid sick or vacation time, and paid wages. Inadequate ES contribute to the labour market vulnerability of workers; however, they are not typically considered to be risk factors for workplace injury. In a sample of Canadian workers, we examine the risk of injury associated with inadequate ES, independent of, and combined with inadequate workplace protections from workplace hazards. Methods: Data from 2,803 adults working 15 hours or more/week in workplaces with at least five employees were analysed. We explored associations between exposure to workplace hazards with inadequate protections [termed occupational health and safety (OHS) vulnerability] and inadequate ES on workplace injury (physical or mental injury; injury requiring time off). Additive interaction models were used to examine the independent and combined effects of these exposures. Results: Occupational health and safety vulnerability and inadequate ES were independently associated with increased injury outcomes. Adjusted models showed an additive relationship for all injury outcomes between OHS vulnerability and inadequate ES. Statistically significant superadditive relationships were observed for physical injury risk with policy and procedure vulnerability plus inadequate ES [synergy index (S) 1.50, 95% CI: 1.13–2.00] and for overall OHS vulnerability plus inadequate ES (S 1.53, 95% CI: 1.16–2.02), suggesting a combined effect greater than independent effects. Conclusion: Occupational health and safety vulnerability and inadequate ES are independently associated with workplace injury. For certain injury outcomes, the combined effect of OHS vulnerability and inadequate ES is greater than the independent effects of each individual exposure.